Research on the relationship between physical activity, sleep quality, psychological resilience, and social adaptation among Chinese college students: A cross-sectional study - Li, Yongbin; Guo, Kelei (Frontiers in Psychology, 2023)
Background: Sleep quality has become a frequent and prominent public health problem in Chinese universities, which seriously hinders the healthy development of college students and the improvement of the quality of higher education. Objective: The purpose of this study is to explore the relationship between physical activity and sleep quality among Chinese college students, and the mechanism of psychological resilience and social adaptation, and provide suggestions for improving the sleep quality among Chinese college students. Methods: From August to September 2022, a cross-sectional survey was conducted by using the convenience sampling method in Guangdong Province.1622 college students were investigated with Physical Activity Scale, Pittsburgh Sleep Quality Index Scale, Psychological resilience Scale and Social Adaptation Diagnostic Scale, of which 893 were male and 729 were female. Use SPSS23.0 and PROCESS plug-ins to analyze data. Results: (1) There was a significant negative correlation between physical activity and sleep quality (r=-0.237), and the direct path of physical activity to sleep quality was significant ( β= -0.236,t= -9.888, p＜0.01)； (2) Physical activity can positively predict psychological resilience (β= 0.215, t=8.823, p ＜ 0.01) and social adaptation (β= 0.164，t=7.773，p＜0.01); Psychological resilience can negatively predict sleep quality (β= -0.337, t=-15.711, p＜0.01), positive prediction of social adaptation（ β= 0.504，t=23.961，p＜0.01); Social adaptation can negatively predict sleep quality (β= -0.405，t=-18.558，p＜0.01)； (3) Psychological resilience and social adaptation play a significant mediating role between physical activity and sleep quality. The mediation effect consists of three paths: physical activity → psychological resilience → sleep quality (mediation effect value is -0.0723), physical activity → social adaptation → sleep quality (mediation effect value is -0.0662), physical activity → psychological resilience → social adaptation → sleep quality (mediation effect value is -0.0438). (4) There is no gender difference in chain mediated effect. Conclusion: (1) Physical activity can significantly positively predict college students' psychological resilience and social adaptation, and negatively predict sleep quality; (2) Physical activity can not only directly affect the quality of sleep, but also indirectly affect the quality of sleep through the independent intermediary role of psychological resilience and social adaptation and the chain intermediary role of both.